Laddered multilevel DC/AC inverters used in Solar Panel Energy systems. Issue 9 (1st November 2013) - Luo, Fang Lin; Ye, Hong
Abstract : Multilevel DC/AC inverters have various structures. They have many advantages. Unfortunately, most existing inverters content too many components (independent/floating batteries/sources, diodes, capacitors and switches). The author introduces the 'laddered multilevel DC/AC inverters' in this study, that is new approach of the development in this area. These inverters use much less components. Their simple structure and clear operation are obviously different from the existing inverters. Its application in Solar Panel Energy systems is successful. The simulation and experimental results strongly support our design. The measured total harmonic distortion illustrates the good quality of output sine wave. The authors believe that these inverters will draw much attention, and be applied in other renewable energy systems.